Information technologies and economic development in Latin America - Chong, Alberto; Yáñez-Pagans, Mónica (Anthem Press, 2020)
'Information Technologies in Latin America' provides a collection of rigorous empirical studies that contributes to a better understanding of the role and impact of old and new information technologies on Latin American economic development through the use of randomized and quasi-experimental methods.